(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of the research study is to determine how teachers’ didactic methods affect students in the virtual learning environment Methods: The objective of this experimental study is to examine the relationship that exists between teachers and university students. The sample was of 150 people, these were sent through a link to be answered by the students, after which the data were processed to know the data of the different participants and the questionnaire that measures the factors of the study. The data collection was done through an online questionnaire in Google Forms; the same that was directed to customers who consume the enterprises, the link of the questionnaire was provided to students and teachers Results: the alternative always teaching strategies reached 50.31%, pedagogical strategies 47.73%, and interactivity with 46.49% the other three dimensions: technological resources 41.22%, educational platforms 46.69% and virtual modality 48.97%. According to these general results, the qualification is very good; to accept or reject the general hypothesis, Spearman’s Rho correlation was performed, finding a high relationship (RS: 0.811) and Sig (0.000), for this reason the null hypothesis is rejected and the alternative hypothesis is accepted. Conclusions: didactic strategies have a significant influence on the virtual learning of students and university teachers.